2014
DOI: 10.1208/s12248-013-9549-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flavonoids Modulate CYP2C to Improve Drug Oral Bioavailability and Their Qualitative/Quantitative Structure–Activity Relationship

Abstract: Abstract. This study aims to improve the drug oral bioavailability by co-administration with flavonoid inhibitors of the CYP2C isozyme and to establish qualitative and quantitative (QSAR) structure-activity relationships (SAR) between flavonoids and CYP2C. A total of 40 naturally occurring flavonoids were screened in vitro for CYP2C inhibition. Enzyme activity was determined by measuring conversion of tolbutamide to 4-hydroxytolbutamide by rat liver microsomes. The percent inhibition and IC 50 of each flavonoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…These findings are supported by several previous studies demonstrated that Nigella sativa's main constituents thymoquinone inhibited CYP2C11 enzyme [2]. In addition, some flavonoids in Trigonella foenum-graecum, such as vitexin, tricin, naringenin, quercetin and tricin-7-O-beta-D-glucopyranoside are known CYP inhibitors [37][38][39]. Moreover, terpenoidal and ferulic acid compounds in Ferula asafoetida are CYP2C modulators [40,41].…”
supporting
confidence: 76%
“…These findings are supported by several previous studies demonstrated that Nigella sativa's main constituents thymoquinone inhibited CYP2C11 enzyme [2]. In addition, some flavonoids in Trigonella foenum-graecum, such as vitexin, tricin, naringenin, quercetin and tricin-7-O-beta-D-glucopyranoside are known CYP inhibitors [37][38][39]. Moreover, terpenoidal and ferulic acid compounds in Ferula asafoetida are CYP2C modulators [40,41].…”
supporting
confidence: 76%
“…For example, De Magalhães et al showed that tea infusions made from various A. annua cultivars inhibited CYP3A4 (Melillo de Magalhães et al, 2012), an enzyme present in the intestine involved in the metabolism of artemisinin (Svensson and Ashton, 1999). Quercetin, a flavonoid found in A. annua , also increased the absorption of doxorubicin in rats (Choi et al, 2011), while tamarixetin, another flavonoid, increased absorption of fluvastatin in rats (Wang et al, 2014). Further, other studies showed that flavonoids found in A. annua , such as quercetin and rutin, inhibited CYP3A4 as well as other cytochrome P450 enzymes that mediate the metabolism of artemisinin (Wang et al, 2014).…”
Section: 0 Introductionmentioning
confidence: 99%
“…Quercetin, a flavonoid found in A. annua , also increased the absorption of doxorubicin in rats (Choi et al, 2011), while tamarixetin, another flavonoid, increased absorption of fluvastatin in rats (Wang et al, 2014). Further, other studies showed that flavonoids found in A. annua , such as quercetin and rutin, inhibited CYP3A4 as well as other cytochrome P450 enzymes that mediate the metabolism of artemisinin (Wang et al, 2014).…”
Section: 0 Introductionmentioning
confidence: 99%
“…Accordingly, oral coadministrations of flavonoids can improve the therapeutic effects of drugs with low bioavailability. [ 59 61 62 ]…”
Section: Resultsmentioning
confidence: 99%